Islamic legal principles in the short anthology "Ujana Rindu". - Kamarudin, Kamariah (Dewan Bahasa dan Pustaka, 2010)
The development of Malay Literature in the country has not been confined to producing writers from the fields of education, journalism and the like. There is a tendency for writers from the legal field to produce literary works. The involvement of these is not limited to writing works based on current law but also includes Islamic elements. This can be seen through the emergence of young writers from the legal field such as Siti Hajar Mohd Zaki, Mohd. Asmadi Saiman and others. Therefore, this article seeks to analyse the Islamic legal principles in the short story collection titled Ujana Rindu, written by two graduated from the International Islamic University Malaysia, Siti Hajar Mohd Zaki and Mohd. Asmadi Saiman (Dewan Bahasa dan Pustaka, 2006). The study clearly shows that both writers' knowledge of the law is utilized to create literary works in line with the legal principles found in the Qur'an and hadith. Ujana Rindu shows the importance of Islamic law in human society, especially where relationships among people (habl min al-Nas) and the relationship between humans and the Creator (habl min Allah) are concerned. This, in the end, will bring about the values of al-Khayr (goodness), al-Haqq (truth) dan aI-Jamal (beauty) in the readers' analysis of a literary work.